2020
DOI: 10.1038/s41598-020-67695-y
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical response of California electricity demand to summer-time temperature variation

Abstract: Current projections of the climate-sensitive portion of residential electricity demand are based on estimating the temperature response of the mean of the demand distribution. In this work, we show that there is significant asymmetry in the summertime temperature response of electricity demand in the state of California, with high-intensity demand demonstrating a greater sensitivity to temperature increases. The greater climate sensitivity of high-intensity demand is found not only in the observed data, but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…While the household‐days metric is estimated for the average household in different domains, the burden will not be equally felt across all households. Previous work has shown that low income households bear the brunt of extreme heat events within cities (Khosla et al., 2020; Sanchez‐Guevara et al., 2019), making them more vulnerable to climate‐induced temperature increases and subsequent electricity outages and blackouts (Khosla et al., 2020; Kumar et al., 2020). This higher vulnerability arises often due to a number of factors—from inferior housing structures and residing in areas with higher urban heat island effects to the inability to afford increasing electricity bills (Drehobl & Ross, 2016; Graff & Carley, 2020; Sánchez‐Guevara et al., 2017, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While the household‐days metric is estimated for the average household in different domains, the burden will not be equally felt across all households. Previous work has shown that low income households bear the brunt of extreme heat events within cities (Khosla et al., 2020; Sanchez‐Guevara et al., 2019), making them more vulnerable to climate‐induced temperature increases and subsequent electricity outages and blackouts (Khosla et al., 2020; Kumar et al., 2020). This higher vulnerability arises often due to a number of factors—from inferior housing structures and residing in areas with higher urban heat island effects to the inability to afford increasing electricity bills (Drehobl & Ross, 2016; Graff & Carley, 2020; Sánchez‐Guevara et al., 2017, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The first of which is the use of domain‐wide mean values within the climate data. There has been previous work using population‐weighted climate data to model electricity consumption (Kumar et al., 2020; Maia‐Silva et al., 2020). However, given that the household air conditioning use data were obtained as domain‐wide means, we opted to maintain a similar structure in the climate data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the electricity demand depends on temperature, a correction needs to be applied to make comparisons meaningful. To this effect, the temperature dependence of the load is derived from multi-annual periods and for specific areas [12,13]. For the mainland grid, such a dependence [14] was updated recently [15] based on data for the 13-year 2006-2018 period, as illustrated in Figure 1, and has been utilized in this analysis.…”
Section: Electricity Consumptionmentioning
confidence: 99%